2010
DOI: 10.1007/s11218-010-9141-z
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration and psychological ownership: how does the tension between the two influence perceived learning?

Abstract: Collaborative writing may evoke conflict between individuals' feeling of contribution and their sense of ownership toward the collective outcomes. The present study tested the relations between perceived psychological ownership, perceived quality of the product, and perceived learning in five experimental conditions: two collaborative, two sharing, and a control. Analysis of the changes made between versions revealed differences in quantity and in types of changes between collaboration, sharing, and control co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 35 publications
2
45
1
8
Order By: Relevance
“…Collaboration within a team can both improve the quality of the outcome (Blau & Caspi, 2009;Caspi & Blau, 2011) and save the time invested on preparing 1:1 lessons. As stated by a teacher from the science department, "We work as a team, so we distribute the work load.…”
Section: Collaboration Among Teachers On Digital Learning Designmentioning
confidence: 99%
“…Collaboration within a team can both improve the quality of the outcome (Blau & Caspi, 2009;Caspi & Blau, 2011) and save the time invested on preparing 1:1 lessons. As stated by a teacher from the science department, "We work as a team, so we distribute the work load.…”
Section: Collaboration Among Teachers On Digital Learning Designmentioning
confidence: 99%
“…"They found differences in psychological ownership, perceived quality of the document, but not in [students'] perceived learning, and believe that a collaboratively written document might have higher quality than a document written alone" (Brodahl et al, 2011, p. 79). They conclude that relation between perceived ownership and perceived learning is mediated by perceived quality of the written product (Caspi, & Blau, 2011) and improvement suggestions preferred over editing one another's writing (Blau, & Caspi, 2009a, 2009b.…”
Section: Positive Elements Of Usementioning
confidence: 99%
“…(Brodahl et al, 2011, p. 74) However the use of Google Docs (2008) and EtherPad (2008), being collaborative writing tools relatively comparable to wikis, remains a gap in research literature (Benson, 2012;Chu & Kennedy, 2011), though recently a number of contributions to the body of research have been made (Brodahl et al, 2011;Burden, 2012;Caspi & Blau, 2011;Cruz, Dominguez, Maia, Pedrosa, & Grams, 2013;Dishaw, Eierman, Iversen, & Philip, 2013;Garner, 2010;Oguilve, Vindas, & Moya, 2012;Tomlinson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…'I enjoyed the interaction with the instructor during the lecture'; Range: 2.67-6.00, Median: 5.00, Mean: 5.07, SD: 0.68, Skewness: −0.73). A previous study (Caspi and Blau 2011) found the following reliability scores for the questionnaire subscales: cognitive subscale α = 0.74, emotional and social subscales α's = 0.90. In the current study, the following reliability scores were found: cognitive subscale α = 0.89, emotional subscale α = 0.76, social subscale: α = 0.77.…”
Section: Tools and Materialsmentioning
confidence: 75%